Establishing a Hybrid Laser Lathing Technology - Sivarao, Subramonian; S.THIRU,, CHITRAMBALAM; T., Joseph Sahaya Anand; Mariana , Yusof (IDOSI Publications, 2013)
Traditional contact lathing is greatly challenged by the rapidly being developed super hard engineering materials. Being the earliest machining process, lathing operation captures 60 % of the total machining processes in most metal cutting industries. This paper reviews the literature related to the available technological solutions for non-contact laser lathing process. It also aims to establish a novel methodology to propose a hybrid non-contact lathing operation using a flatbed CO laser cutting machine.While exposing 2 the various techniques of laser lathing, preliminary empirical work conducted shows a promising future of hybridizing CO laser flat cutting into laser lathing process. The summary of this paper is expected to create a 2 leap in laser machining process towards developing a hybrid laser processing of materials involving transformation of 2D flat cutting into 3D laser turning to cater the market of precision machining.